Al-Shabaab's leadership hierarchy and its ideology - Shuriye, Abdi Omar (SAVAP International, 2012)
This research studies the deriving ideology and directions of al-Shabaab movement. The organization constitutes obdurate and dogmatic elements and individuals of originally Somali’s Salafi movements. The initial findings of this research are that al-Shabaab’s ideology must have originated outside Somalia. The key objective of this research is to investigate al-Shabaab’s political ideology and its structural leadership, to assess the ideological relationship between al-Shabaab and Al-Qaeda, to comprehend the political future of the group and to ascertain their political and theological ideologies. The research therefore investigates the leadership structure of al-Shabaab and its organizational settings. The methodology of this research, partly, involved collecting field data in a form of informal interviews and surveys, but it is mainly an analytical and evaluative approach. My findings indicate that al-Shabaab operate in a flexible multiple cells organizational leadership structure whose components are independent.